An approach for risk assessment of rail defects - Kumar S.; Gupta S.; Ghodrati B.; Kumar U. (My University, 2025)
Rail defects appear in a greater variety and frequency due to higher axle loads and increasing traffic density in passenger and freight trains. Many of these rail defects, if left undetected, can develop into rail breaks, which may lead to train derailments. Reduction in the number of such catastrophic events requires huge investments on inspection and maintenance activities. Therefore proper maintenance planning and risk assessment is required to reduce the rail maintenance cost without compromising safety. In this paper, an approach has been developed for risk assessment of rail defects to support the decision-making process during scheduling of rail inspection and grinding frequency, based on the type of defect and its risk of occurring and developing into a rail break. The approach will help in increasing the safety of passengers and rolling stock as well as reducing the overall rail maintenance cost, as it helps in making effective decisions related to inspection frequency (i.e. resource allocation according to the need). The approach is presented with the aid of a case study from the Swedish National Rail Administration (Banverket). Both, quantitative and qualitative analysis technique has been used in this paper to assess the risk of occurrence of a rail defect and its development into a rail break. © 2010 World Scientific Publishing Company.